Periphyton in urban freshwater facilitates transformation of trace organic compounds: A case study on iodinated contrast media - Mauch, Jonas; Kronsbein, Anna Lena; Putschew, Anke; Lewandowski, Jörg; Hilt, Sabine (Frontiers in Environmental Science, 2023)
Due to urbanization and demographic change trace organic compounds (TrOCs), synthetic chemicals such as pharmaceuticals, personal care products or biocides are an increasing problem in waterbodies affected by treated sewage. This contamination is particularly relevant when surface water is used for drinking water production, either directly or by bank filtration. Removal and transformation of TrOCs are affected by a variety of processes, and we hypothesize that periphyton, the mixture of photo- and heterotrophic biota attached to submerged surfaces of aquatic ecosystems, can facilitate TrOC transformation. Here we experimentally tested the influence of periphyton on different substrates on the transformation of iodinated contrast media (ICM). These hydrophilic compounds are problematic due to their poor removal by conventional wastewater treatment and high persistence of the triiodinated benzoic acid within aquatic environments. We added 100 µg L-1 of three ICM, iopromide (IOP), iopamidol (IOM) and diatrizoate (DIA) to batch experiments containing periphyton on artificial substrates or on invasive quagga mussels and to a column experiment with periphyton, quagga mussels and sediment from a bank filtration site in a lake. IOP concentrations were reduced by up to 93% after 30 days in batch experiments with periphyton on artificial substrates and completely in treatments with mussels and periphyton. In contrast, no concentration decrease was observed for IOM and DIA. IOP reduction was positively correlated with periphyton biomass ranging from 0.7 to 9.2 g dry weight m-2 and negatively correlated with oxygen saturation. 9 of 12 known aerobic IOP transformation products frequently occurring in treated wastewater were found. We suggest that periphyton facilitated IOP transformation by providing substrate for bacterial growth and enhanced bacterial growth rates due to algal photosynthesis, a co-oxidation catalyzed by ammonia oxidizing bacteria and by a stimulatory influence of labile carbon produced by periphytic algae on the microbially mediated decomposition of IOP. Periphyton is facilitated by increased nutrient supply of dense mussel stands or by an increased surface area provided in dense macrophyte stands. Consequently, changes in the abundance of these littoral communities by invasion or management can affect TrOC transformation and thus water quality for drinking water production from urban freshwaters.